The Survival Processing Advantage of Face: The Memorization of the (Un)Trustworthy Face Contributes More to Survival Adaptation. (1st April 2019) - Hou, Chunna; Liu, Zhijun
Researchers have found that compared with other existing conditions (e.g., pleasantness), information relevant to survival produced a higher rate of retrieval; this effect is known as the survival processing advantage (SPA). Previous experiments have examined that the advantage of memory can be extended to some different types of visual pictorial material, such as pictures and short video clips, but there were some arguments for whether face stimulus could be seen as a boundary condition of SPA. The current work explores whether there is a mnemonic advantage to different trustworthiness of face for human adaptation. In two experiments, we manipulated the facial trustworthiness (untrustworthy, neutral, and trustworthy), which is believed to provide information regarding survival decisions. Participants were asked to predict their avoidance or approach response tendency, when encountering strangers (represented by three classified faces of trustworthiness) in a survival scenario and the control scenario. The final surprise memory tests revealed that it was better to recognize both the trustworthy faces and untrustworthy faces, when the task was related to survival. Experiment 1 demonstrated the existence of a SPA in the bipolarity of facial untrustworthiness and trustworthiness. In Experiment 2, we replicated the SPA of trustworthy and untrustworthy face recognitions using a matched design, where we found this kind of memory benefits only in recognition tasks but not in source memory tasks. These results extend the generality of SPAs to face domain.